FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAYANAN PUBLIK DI KANTOR KECAMATAN MAMAJANG - indra wijaya (Jurnal Inovasi dan Pelayanan Publik Makassar, 2022)
This research was conducted to find out, describe, and explain regarding the quality of public services in the Mamajang District Office using qualitative research methods with a descriptive approach. Data collection techniques, interviews, observation, and documentation, interactive model data analysis Miles, Huberman, & Saldana (2014). The results of the study show that the quality of public services at the Mamajang District Office has been running quite well. it is necessary to make improvements by the sub-district staff and the Mamajang sub-district office in terms of service quality. a) Improving service infrastructure; b) Leaders of the Mamajang District Office should provide training/workshops on excellent public services; c) Controlling employee performance through measurement of community satisfaction index; and d) Able to be consistent in providing services in accordance with public service hours so that the services provided can run well.